2020
DOI: 10.48550/arxiv.2011.01832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Goal recognition via model-based and model-free techniques

Abstract: Goal recognition aims at predicting human intentions from a trace of observations. This ability allows people or organizations to anticipate future actions and intervene in a positive (collaborative) or negative (adversarial) way. Goal recognition has been successfully used in many domains, but it has been seldom been used by financial institutions. We claim the techniques are ripe for its wide use in finance-related tasks. The main two approaches to perform goal recognition are model-based (planningbased) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…We evaluated four different data-driven methods: The NBM presented earlier in Section 5 and three additional data-driven approaches, which were selected following a recent study by Borrajo et al (Borrajo, Gopalakrishnan, & Potluru, 2020). Specifically, we used K-Nearest-Neighbors (KNN) (Russell, 2016, pp.…”
Section: Data-driven Goal Recognition Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated four different data-driven methods: The NBM presented earlier in Section 5 and three additional data-driven approaches, which were selected following a recent study by Borrajo et al (Borrajo, Gopalakrishnan, & Potluru, 2020). Specifically, we used K-Nearest-Neighbors (KNN) (Russell, 2016, pp.…”
Section: Data-driven Goal Recognition Methodsmentioning
confidence: 99%
“…First, we used a binary encoding of the planning states, consisting of the state of all planning fluents. Second, following the work of Borrajo et al (Borrajo et al, 2020), we used a vector encoding of the observed action sequence.…”
Section: Data-driven Goal Recognition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial intelligence and machine learning have advanced rapidly, leading to the emergence of a new paradigm for goal recognition based on learning theory. This paradigm can be categorized into two broad groups: model-based and model-free approaches, based on the learning method employed [27,28].…”
Section: Goal Recognition As Learningmentioning
confidence: 99%
“…In contrast, model-free goal recognition based on learning requires no model and only utilizes the observed action sequence and initial state as input. Borrajo et al [27,33] studied goal recognition using XGBoost and LSTM neural networks, which only employ observation sequences without any domain knowledge. However, they trained specific machine learning models for each goal recognition instance and used specific instance datasets for training and testing.…”
Section: Goal Recognition As Learningmentioning
confidence: 99%